Cardiorespiratory Fitness in Youth: An Important Marker of Health. Issue 7 (18th August 2020) - Raghuveer, Geetha; Hartz, Jacob; Lubans, David R.; Takken, Timothy; Wiltz, Jennifer L.; Mietus-Snyder, Michele; Perak, Amanda M.; Baker-Smith, Carissa; Pietris, Nicholas; Edwards, Nicholas M.
Abstract : Cardiorespiratory fitness (CRF) refers to the capacity of the circulatory and respiratory systems to supply oxygen to skeletal muscle mitochondria for energy production needed during physical activity. CRF is an important marker of physical and mental health and academic achievement in youth. However, only 40% of US youth are currently believed to have healthy CRF. In this statement, we review the physiological principles that determine CRF, the tools that are available to assess CRF, the modifiable and nonmodifiable factors influencing CRF, the association of CRF with markers of health in otherwise healthy youth, and the temporal trends in CRF both in the United States and internationally. Development of a cost-effective CRF measurement process that could readily be incorporated into office visits and in field settings to screen all youth periodically could help identify those at increased risk.